2006
DOI: 10.21273/hortsci.41.2.437
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effects of NaCl and CaCl2 Salinity on Cucumber Grown in a Closed Hydroponic System

Abstract: The objective of this study was to discriminate among Na, Cl, and Ca salinity effects on cucumber (Cucumis sativus L.). Cucumber plants grown in perlite were exposed for 134 days to low and moderate levels of salinity induced by the addition of either NaCl or CaCl2 at equal rates (on a chemical equivalent basis) to a standard nutrient solution for cucumber up to two target electrical conductivity (EC) levels (3.0 and 5.0 dS·m–1). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 26 publications
(44 reference statements)
4
23
2
Order By: Relevance
“…The reports on reduction in fruit yield under salt stress conditions by Shaterian et al (2005) in Solanum tuberosum, Bustan et al (2005) in melon, and Trajkava et al (2006) in cucumber also supported the present findings. High salt stress not only imposes osmotic and ionic stress on plant, it also influences the uptake and transport of essential nutrients such as K ?…”
Section: Fruit Yield and Fruit Yield Reductionsupporting
confidence: 91%
“…The reports on reduction in fruit yield under salt stress conditions by Shaterian et al (2005) in Solanum tuberosum, Bustan et al (2005) in melon, and Trajkava et al (2006) in cucumber also supported the present findings. High salt stress not only imposes osmotic and ionic stress on plant, it also influences the uptake and transport of essential nutrients such as K ?…”
Section: Fruit Yield and Fruit Yield Reductionsupporting
confidence: 91%
“…Rather than Cl -, Na + has been reported as the primary cause of salt damage in cucumber. This appears to be the reason for the accumulation of a large amount of Cl -in Chaojiquanwang, while showing a lower degree of growth inhibition (Trajkova et al 2006). The present study demonstrated the importance of osmotic components, while taking into consideration the salt tolerance mechanism of grafted plants.…”
Section: Discussionsupporting
confidence: 55%
“…6). This result was not in agreement with results from several previous studies (Trajkova et al, 2006;Huang et al, 2009). Different environmental conditions between these studies may explain the discrepancy.…”
Section: Response Of Fruit Yield and Quality To Sbr Application Undercontrasting
confidence: 99%
“…Different environmental conditions between these studies may explain the discrepancy. Trajkova et al (2006) investigated effects of NaCl salinity on the fruit quality of cucumber grown in a closed hydroponic system, while Huang et al (2009) studied effects of NaCl stress on the fruit quality of cucumber grown in a substrate medium (a mix of peat, vermiculite and perlite). In this study, cucumber plants were grown in field soils, which showed different physicochemical and biological properties compared to soilless cultivation conditions used by Trajkova et al (2006) and Huang et al (2009).…”
Section: Response Of Fruit Yield and Quality To Sbr Application Undermentioning
confidence: 99%
See 1 more Smart Citation